(untitled) (Green Life Medical College Journal, 2025)
Adenoid cystic carcinoma (ACC) is predominantly a malignant neoplasm of the salivary glands but rarely can develop in the lungs as a primary tumor from bronchial glands, accounting for only 0.04%– 0.2% of all pulmonary malignancies. Its slow growth, infiltrative nature, and nonspecific respiratory symptoms often mimic other conditions, creating considerable diagnostic and therapeutic challenges. We report a case of a 50-year-old male radiotechnologist presented with recurrent hemoptysis and unintentional weight loss. Despite a normal chest X-ray, HRCT revealed a 4 × 3.1 cm soft tissue lesion completely obstructing the right principal bronchus with collapse of the right lower lobe. Pathological evaluation of bronchoscopic samples confirmed adenoid cystic carcinoma, necessitating a right lower bilobectomy. Subsequent histopathological examination revealed an intermediategrade ACC with classic cribriform patterns, without lymphovascular and perineural invasion, and involvement of the middle lobe bronchial margin (stage pT1b pNx pMx). Margin positivity raised concerns for potential recurrence, highlighting the need for meticulous follow-up and consideration of adjuvant therapy. This case emphasizes the importance of histopathological confirmation, margin assessment, and long-term surveillance in managing this rare pulmonary malignancy. Journal of Green Life Med. Col. 2025; 10(2): 62- 65